MiR-144-3p Targets FoxO1 to Reduce Its Regulation of Adiponectin and Promote Adipogenesis - Lin, Weimin; Tang, Yonghang; Zhao, Yuelei; Zhao, Jindi; Zhang, Lifan; Wei, Wei; Chen, Jie (Frontiers in Genetics, 2020)
MicroRNAs (miRNAs), as an important short-chain non-coding RNA, is demonstrated to play the important post-transcriptional role in many biological activities, including adipogenesis. The miR-144 is identified to significantly up-regulated in type II diabetes (T2D), and even it is considered to be an important biomarker for T2D. However, although the T2D occurred is inextricably linked to adipogenesis, the role of miR-144 directly regulating adipogenesis remains to be further explored. In this paper, we demonstrate miR-144 has a higher expression level in porcine high backfat group, and it has a significant positive effect on promoting the differentiation of pre-adipocytes. FoxO1 is a target gene of miR-144, furthermore, FoxO1 inhibits the differentiation of pre-adipocytes. On the other hand, we demonstrate FoxO1 can bind to AdipoQ gene promoter, then regulates the AdipoQ expressed by binding to the FoxO1 binding site in AdipoQ promoter -310 ~ -300bp region. Meanwhile, miR-144 and FoxO1 co-expressional research also shows both factors regulate the adipogenesis. To sum up, our research indicates miR-144 targets FoxO1, thus reduces its expression and inhibits its promotional effect on adiponectin, thereby alleviates the inhibitory effect of adiponectin on adipogenesis.